Deformation behavior and microstructure evolution of one novel superalloy with high rare earth gadolinium content: Multi-scale modeling and experimental study - Xin Fu; Qing-Chun Zhu; Wen-Bin Chen; Li Jiang; Fang Liu; Zhi-Jun Li (Journal of Materials Research and Technology)
It has been proved that rare earth elements have a positive effect on the performance of superalloys and steels at only trace levels, but rare earth phases are always tricky in the manufacturing process. In this work, one Ni–Mo–Cr-Gd alloy with ultrahigh rare earth Gd content (1.75 wt %) was designed to reveal the influence of hard and brittle Ni5Gd particles on hot deformation behavior and microstructure evolution. The Ni–Mo–Cr-Gd alloy exhibits higher deformation activation energy and smaller processable regions in the processing maps as compared with the Ni–Mo–Cr alloy. Combining electron back scatter diffraction and crystal plastic finite element method, it was found that strain concentrates around Ni5Gd particles, especially at grain boundaries, and rapidly reaches the critical value for recrystallization, which verifies particle stimulated nucleation. The recrystallization fraction decreases with strain rates from 0.01 to 1 s−1 but increases from 1 to 10 s−1, which is because meta-dynamic recrystallization occurs faster when the strain rate is greater than 1 s−1 and Ni5Gd particles promote the process indirectly by introducing more severely deformed matrix. Furthermore, the finite element modeling shows that plastic strain and temperature rise at the central region of samples increase with strain rate increasing, which can explain the unusual fragmentation of Ni5Gd at 1200 °C with the highest strain rate. Our results firstly reveal the evolution mechanism of Gd-containing superalloy during hot deformation, which can help to solve the manufacturing problems of similar alloys.